Body pedagogics: embodied learning for the health professions. Issue 10 (19th June 2019) - Kelly, Martina; Ellaway, Rachel; Scherpbier, Albert; King, Nigel; Dornan, Tim
Abstract : Medicine as Embodied Practice: Bodily dysfunctions bring patients to their doctors and even diseases of the mind can originate in patients' bodies. Doctors respond by using their own bodies – hands, eyes, ears and sometimes noses – to make diagnoses and treat diseases. Yet, despite the embodied nature of practice, medicine typically treats the body as an object, paying scant attention to the subjective embodied experiences of patients and doctors. Much health professions education (HPE) reflects this, prioritising cognition over learners' sense of embodiment. Hence there is a gap between the embodied realities of practice and the disembodied nature of medical education. This article introduces readers to 'body pedagogics' as a framework that can help to re‐establish embodiment as a central principle of HPE. Body Pedagogics: This embodiment theory, drawn from sociology, anthropology and phenomenology, has informed such disparate fields as glassblowing education and military training. Body pedagogics emphasises learning as a physically embodied process. It illustrates how multisensory experience causes embodied changes that become an automatic part of physician expertise. We introduce core body pedagogic concepts using physical examination as an example, examining the bodily means of HPE, students' bodily experiences and the resulting bodily changes. Implications: Body pedagogics can help us to focus attention on embodiment as a central principle of HPE that transcends the discipline‐specific teaching of clinical skills. Moreover, it provides a set of conceptual foundations for an interdisciplinary practice within HPE with implications for instructional design. Body pedagogics can also help us to make strange the habits and disregarded aspects of embodied learning and in so doing help us to consider embodiment more critically and directly in practice and education, and in the ways we research them. Abstract : In the lastest instalment of the Cross‐cutting edge series, Kelly et al. explore how physical experiences of learning shape health professional practices.